The Diversity of Singing Birds at the Way Canguk Research Station, Bukit Barisan Selatan National Park - Andriyani, Agista; Nurcahyani, Nuning; Susanto, Gregorius Nugroho; Sibarani , Marsya Christyanti; Utoyo , Laji (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2022)
Birds have an important role in controlling natural ecosystems. The presence of hunting traces every year indicates hunting at the Way Canguk Research Station. If this happens continuously, it can cause a decrease in the diversity and population of chirping birds. Therefore, this research needs to be carried out to determine the diversity, evenness, richness, relative density, as well as environmental factors that affect the chirping bird community, and the intensity of bird hunting in SPWC. The research was conducted at the Way Canguk Research Station, Bukit Barisan Selatan National Park, using the point count method.